Faculty perspectives on research and extension in higher education: a mixed-methods study - Patalinghug, Haidee Fuentes; Patalinghug, Mark Erana (Intelektual Pustaka Media Utama, 2026)
This research employed an exploratory sequential mixed-methods design to comprehensively investigate the research and extension (RE) functions within a higher education institutions (HEIs). The study unfolded in 2 distinct phases, commencing with a qualitative exploration of HEIs faculty perspectives from one of the HEIs in Zamboanga del Sur, Philippines. This qualitative phase, facilitated by expert-validated in-depth interviews (IDI), uncovered insights into faculty experiences, challenges, and potential interventions related to RE functions. The qualitative data were collected through the interview of 5 purposively selected faculty as participants of the study using semi-structured interview guide questions. Transitioning seamlessly, the subsequent quantitative phase involved 31 participants across academic ranks, assessing faculty productivity, knowledge, and skills in these functions. Stringent validation processes, including expert validation of interview protocols and statistical reliability checks for survey instruments, underscored the research’s methodological rigor. Despite faculty recognition of the value of RE, engagement remained compliance-driven, revealing underlying challenges such as limited expertise and institutional expectations. Proposed interventions centered on mentoring, skill development, and creating a supportive environment. Proficiency gaps identified in statistical tools and international conference presentations suggested targeted training needs. The study underscored the importance of aligning faculty engagement with intrinsic motivation and institutional goals, paving the way for future investigations into motivational influences and the intricate dynamics of RE practices in HEIs.